Resistance of Nilaparvata lugens to Fenobucarb and Imidacloprid and Susceptibility to Neem Oil Insecticides - Danar Dono; Neneng S Widayani; Safri Ishmayana; Yusup Hidayat; Fitri Widiantini; Ceppy Nasahi (HAYATI Journal of Biosciences, 2022)
This study aims to monitor and determine the level of resistance of N. lugens to fenobucarb and imidacloprid, to analyse of the specific activities of asetylcholinesterase, Glutation S-Transferase, esterase, and to determine sensitivity of resistant N. lugens to the neem oil. Resistance tests were conducted on a field population from Cipunagara, Subang, West Java, Indonesia, and a standard population originating from Banyuwangi, East Java, that was obtained from the Indonesian Center for Rice Research. Synthetic and neem Insecticides were applied using the leaf-stem dipping method. The resistance ratio obtained by comparing the LC50 value of the field population with the standard. The test insects were considered to be resistant to synthetic insecticide if they had a resistance ratio (RR) of more than 4, indicated resistance if RR ≥1, and susceptible to neem if has RR <1. The results of the research showed that the N. lugens population of Cipunagara indicated resistance to fenobucarb (RR = 2.43), while it was clearly resistance to imidacloprid (RR = 13.95). Specific activities of the acetylcholinesterase and Glutathione S-Transferase of the N. lugens Cipunagara populations were higher than the standard, while the esterase specific activity was lower. These two enzymes are responsible for the resistance of N. lugens to fenobucarb and imidacloprid. Nevertheless, the N. lugens population of Cipunagara was susceptible to neem (RR <1) that never been reported before. Therefore, it is important to know the change in the sensitivity of the target and the metabolic pathway of the insecticide used to manage insect resistance.